UNA NUEVA ESPECIE CHILENA DE LEIOPROCTUS (SPINOLAPIS) (HYMENOPTERA: COLLETIDAE) - Toro, Haroldo (Acta Entomológica Chilena, 2022)
In this work a new species of Leioproctus (Spinolapis) from the central zone of Chile is described.